Differences in the COMPUSTAT and Expanded Value Line Databases and the Potential Impact on Empirical Research. - Kern, Beth B.; Morris, Michael H. (The Accounting Review, 1994)
Abstract Compares COMPUSTAT and Value Line databases in terms of financial data and size of firm distribution. COMPUSTAT and Value Line data assimilation policies; Effects of the differences in the two databases on population of firms' inferences; Importance of selecting databases and variables from those databases.